Pengaruh Suhu dan Waktu Pengeringan Terhadap Fisikokimia Tepung Pisang Mas - Manggabarani, Saskiyanto; Tanuwijaya, Rani Rahmasari; Febriyanti, Lilian (Sekolah Tinggi Ilmu Kesehatan Pertamedika, 2023)
Mas banana has the potential to be developed into flour products due to its starch, fiber, and functional compound content. This study aims to analyze the effect of various heating temperatures on the physicochemical properties of Mas banana (Musa acuminata) flour. The research design used was a one-factor Completely Randomized Design (CRD) with four treatments, namely without heating (P0), oven heating at 60°C for 6 hours (P1), 80°C for 4 hours (P2), and 100°C for 2 hours (P3), each repeated three times. The parameters analyzed included moisture, ash, protein, fat, carbohydrate, mineral (potassium and magnesium) content, and functional properties in the form of water absorption capacity (WAC) and oil absorption capacity (OAC). The results showed that increasing the heating temperature decreased the moisture, protein, and fat content significantly (p < 0.05), while the ash and carbohydrate content increased. The potassium and magnesium content decreased by approximately 15% and 13%, respectively, due to mineral volatility during heating. WAC and OAC values increased with increasing temperature, indicating partial starch gelatinization and protein denaturation, which increased water and oil binding capacity. Darkening of the flour color at higher temperatures indicates the Maillard reaction and pigment degradation. Heating at 80°C for 4 hours (P2) produced flour with the best characteristics—low moisture content, bright color, and optimal functional properties. Therefore, medium-temperature drying is recommended to produce high-quality banana flour that is physically stable and nutritionally sound, and has potential for use in functional food product formulations.